2020
DOI: 10.1155/2020/9463648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flash Glucose Monitoring on Dietary Variety, Physical Activity, and Self-Care Behaviors in Patients with Diabetes

Abstract: The aim of this study was to evaluate the effects of flash glucose monitoring on dietary variety, physical activity, and self-care behavior in patients with diabetes. This study included outpatients with diabetes using insulin who presented at the Department of Diabetes and Metabolism of the Ise Red Cross Hospital. Before initiating flash glucose monitoring and 12 weeks after its initiation, blood glucose-related parameters were assessed and self-administered questionnaires were completed (Dietary Variety Scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…While these support our present findings on the positive effects of switching to flash glucose monitoring, T2D is of course a distinct entity with unique aetiologies and thus demands its own body of evidence that is apposite to Saudi Arabia. Our findings are supported by a number of observational studies, registries, and a limited number of RCTs (Randomized controlled trial) conducted elsewhere [2][3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 80%
“…While these support our present findings on the positive effects of switching to flash glucose monitoring, T2D is of course a distinct entity with unique aetiologies and thus demands its own body of evidence that is apposite to Saudi Arabia. Our findings are supported by a number of observational studies, registries, and a limited number of RCTs (Randomized controlled trial) conducted elsewhere [2][3][4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 80%
“…More than 425 million people continued living with diabetes in 2017, and people with diabetes are predicted to extend to 693 million by 2045 [20,21]. It is calculated that there will be 300 million diabetes people by 2025 [11], and by 2030, around 366 million people will have type II diabetes mellitus [9]. The prevalence of diabetes in Iran is 3.0, 5.8, 10.8, 14.0% in men and 3.0, 7.0, 14.0, and 19.4% in women aged 25-34, 35-44, 45-54, and 55-64 years, respectively [16].…”
Section: Type II Diabetesmentioning
confidence: 99%
“…It is essential for those who have Type II diabetes to manage self-care behaviors to optimize their treatment outcomes [8]. Some studies investigated the relationship between health literacy and self-care behaviors [9][10][11] and reported discrepant results. Reisi et al concluded that self-care behaviors were signi cantly associated with health literacy.…”
Section: Introductionmentioning
confidence: 99%
“…More than 425 million people continued living with diabetes in 2017, and people with diabetes are predicted to extend to 693 million by 2045 [20,21]. It is calculated that there will be 300 million diabetes people by 2025 [11], and by 2030, around 366 million people will have type II diabetes mellitus [9]. The prevalence of diabetes in Iran is 3.0, 5.8, 10.8, 14.0% in men and 3.0, 7.0, 14.0, and 19.4% in women aged 25-34, 35-44, 45-54, and 55-64 years, respectively[16].…”
Section: Type II Diabetesmentioning
confidence: 99%
“…It is essential for those who have Type II diabetes to manage self-care behaviors to optimize their treatment outcomes [8]. Some studies investigated the relationship between health literacy and self-care behaviors [9][10][11] and reported discrepant results. Reisi et al concluded that self-care behaviors were signi cantly associated with health literacy.…”
mentioning
confidence: 99%